2020
DOI: 10.1007/978-3-030-62784-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Social Transformation - Industry 4.0

Abstract: The impact of advanced infrastructure and the rapidly rising production technologies on the industry have caused the desire for faster but less costly production, leading to Industry 4.0. This study addresses the general concepts in Industry 4.0, our country’s position in the Industry 4.0 processes, changes to be caused by Industry 4.0 in the society and Project Management of these changes. Also, the data from the OECD and Dijital Dönüşüm Derneği (Digital Transformation Association) will be interpreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that organizations that have agility will be able to adopt Industry 4.0 technologies, and once adopted, the capability of agility will become highly dynamic [144,147,148]. In the following section, the major aspects of agility are discussed with respect to Industry 4.0, as suggested by [147,[149][150][151].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%
“…Therefore, it can be concluded that organizations that have agility will be able to adopt Industry 4.0 technologies, and once adopted, the capability of agility will become highly dynamic [144,147,148]. In the following section, the major aspects of agility are discussed with respect to Industry 4.0, as suggested by [147,[149][150][151].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%